DAMPAK MOTIVASI, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP PENINGKATAN KINERJA PEGAWAI DI LINGKUNGAN SEKRETARIAT DAERAH KABUPATEN TEMANGGUNG - Dian Nurhening; Insiatiningsih Insiatiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to analyze the impact of motivation, work discipline and job satisfaction on improving employee performance in the Regional Secretariat of Temanggung Regency. The research method used was quantitative and qualitative where this research was conducted at the Regional Secretariat of Temanggung Regency with a sample of 64 employees as respondents. The research data was obtained through collecting questionnaire results which were distributed directly and interviews through Focus Group Discussion (FGD) to respondents in the Temanggung Regional Secretariat. The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used multiple linear regression analysis and the data was processed with SPSS software. The research questionnaire consists of 45 question items, which contain independent variables namely Work Motivation (X1), Work Discipline (X2), Job Satisfaction (X3) and the Dependent Variable (Y) in this study is performance. The method used for sampling is simple random sampling technique, namely the sampling of members of the population is done randomly and all respondents are considered the same or homogeneous without regard to strata in the population such as gender, age, rank and so on. The results of the multiple linear regression analysis yield the following equation Y = 24.065 + 0.148 X1 – 0.031 X2 + 0.427 X3 meaning that the job satisfaction variable has the most dominant influence on employee performance, which is the result of a regression coefficient of 0.427. Then followed by the second variable that affects the performance variable, namely work motivation with a regression coefficient of 0.148. Whereas the work discipline variable has no effect on performance, because the regression coefficient is -0.031. The results of the F test show that together the independent variables namely motivation, work discipline and job satisfaction affect performance because they have an F-count of 7.686 greater than the F-table of 2.76 and a significant value of 0.000 which is smaller than alpha (0.05). Because the F-value greather than F-table, Ha is accepted, and the first hypothesis is proven. The results of the t test analysis found that the most dominant variable was job satisfaction (X3), that is, when viewed from the beta value of the job satisfaction variable (X3), the greatest value was 0.513. In addition, it was also obtained that the t-count of the variable of job satisfaction has the greatest value of the t-count of other variables and is also greater than the t-table of 1.998, where the t-count of the variable of job satisfaction is 3.821. From the results of this t test proves that the second hypothesis, namely job satisfaction has the greatest impact on improving employee performance, proven and accepted.